2020
DOI: 10.2147/dddt.s258571
|View full text |Cite
|
Sign up to set email alerts
|

<p>Promising Swellable Floating Bupropion Tablets: Formulation, in vitro/in vivo Evaluation and Comparative Pharmacokinetic Study in Human Volunteers</p>

Abstract: Purpose Bupropion is an antidepressant drug that facilitates weight loss. It is a highly water-soluble drug that needs multiple dosing, so it is considered a potential candidate for oral controlled-release dosage form. The aim of this research was to formulate and evaluate satiety-inducing swellable floating bupropion tablets by direct compression targeting depression associated with eating disorders. Various combinations of natural and semi-synthetic hydrogels were selected to achieve maximum swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…High R 2 values, displayed in Table 5 , as well as good agreement between the adjusted R 2 and the predicted R 2 show that data were best fitted to the chosen models. In addition, high adequacy of the chosen models was confirmed by adequate precision values > 4 [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…High R 2 values, displayed in Table 5 , as well as good agreement between the adjusted R 2 and the predicted R 2 show that data were best fitted to the chosen models. In addition, high adequacy of the chosen models was confirmed by adequate precision values > 4 [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies revealed that bupropion able to improve hyperphagic depressed individuals and overweight or obese patients with depression [51][52][53][54][55]. The efficacy of bupropion and sertraline in the treatment of BED and comorbid depression was comparably evaluated in a 24-week retrospective cohort study [56].…”
Section: Norepinephrine-dopamine Reuptake Inhibitorsmentioning
confidence: 99%
“…The dissolution study of floating tablets was conducted using a 6 vessel USP type II dissolution apparatus containing 900 mL of freshly prepared 0.1N HCl maintained at pH 1.2 [20,21]. The bath temperature was set at 37 ± 0.5 • C. One tablet in each vessel was placed and the apparatus was started with a paddle speed of 50 rpm.…”
Section: In Vitro Dissolution Studiesmentioning
confidence: 99%